2005
DOI: 10.1111/j.1525-1438.2005.00270.x
|View full text |Cite
|
Sign up to set email alerts
|

Uterine liposarcoma in a young woman: a case report

Abstract: Liposarcoma of uterus is a very rare neoplasm encountered generally in the sixth or seventh decade of life. We reported the eighth case of uterine liposarcoma with extension to broad ligament in a 23-year-old woman who presented with pelvic pain, dysuria, and rapidly enlarging pelvic mass. During laparotomy, the mass was detected to be originated from the uterine cervix. In frozen section, no definitive diagnosis was established, and for preservation of fertility, extirpation of the mass was performed. The his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Abnormal vaginal bleeding was the most common presentation, 4,14,25,31,41,43 and other symptoms included pelvic pain, increasing abdominal girth, dysuria, weight loss, and constipation. 4,14,18,20,39 Only 1 of 3 of our patients presented with uterine bleeding. The diagnoses of the previously reported 10 uterine liposarcomas were based strictly on histopathologic and immunohistochemical findings.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Abnormal vaginal bleeding was the most common presentation, 4,14,25,31,41,43 and other symptoms included pelvic pain, increasing abdominal girth, dysuria, weight loss, and constipation. 4,14,18,20,39 Only 1 of 3 of our patients presented with uterine bleeding. The diagnoses of the previously reported 10 uterine liposarcomas were based strictly on histopathologic and immunohistochemical findings.…”
Section: Discussionmentioning
confidence: 81%
“…To date, 10 cases within the uterus 4,14,18,20,25,31,32,39,41,43 have been described in the literature. Patients with uterine liposarcomas have ranged in age from 23 to 78 (mean, 56) years, which is similar to the age range found in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In this case, the tumor was totally separated from the uterus and arose within the leaves of the broad ligament and, therefore, could not be labelled as a uterine liposarcoma. The tumor margins were free.…”
Section: Rahimimentioning
confidence: 92%
“…In a review of the literature, Karateke et al identified five cases of pure liposarcoma origi nating from the cervix including their own case [21]. Two were pleomorphic, one was round cell, one was well differentiated, and one was round and myxoid.…”
Section: Editorialmentioning
confidence: 99%